From Co-Teaching to Virtual Reality: The Transformative Potential of Multidisciplinary Education: - Malizal, Zelynda Zeinab (Sinergi International Journal of Education, 2023)
The growing complexity of educational and professional challenges highlights the need for multidisciplinary approaches in higher education. This review synthesizes recent evidence on their integration, effectiveness, and challenges across diverse contexts. Literature was systematically retrieved from Scopus, Web of Science, and Google Scholar using keywords such as multidisciplinary education, interdisciplinary learning, transdisciplinary approaches, educational practice, and collaborative learning. Inclusion criteria focused on peer-reviewed studies within the last fifteen years that examined multidisciplinary design, implementation, or outcomes. Findings revealed that integrative models such as problem-based learning and co-teaching significantly enhanced students’ problem-solving, collaboration, and critical thinking skills. Digital technologies, including Virtual Reality and Learning Analytics, were shown to facilitate experiential learning and provide data-driven feedback, although disparities in access limited their global applicability. In health education, multidisciplinary teams improved clinical competence and interpersonal collaboration, while systemic barriers such as rigid institutional frameworks, insufficient resources, and cultural hierarchies constrained wider adoption, particularly in developing contexts. Policy frameworks and institutional leadership were identified as key enabling factors, with European models offering examples of effective integration. Despite these advances, gaps remain in longitudinal research and comparative cross-national studies. The review concludes that deliberate policy reforms, investment in infrastructure, and faculty development are necessary to overcome barriers and fully realize the transformative potential of multidisciplinary education.